The nominal style in the modern French poetry - Abed, Elaf Hussein (Al-Adab Journal, 2020)
Using the nominal style in the poetry writing is considered a turning point in the history of French poetry, which has witnessed major changes since the mid-nineteenth century, weather at the level of language and form or at the level of subjects. That this method based on the omission of the verb taken from the name the basic core in expressing the topic of the sentence formed a great controversy for linguists in theory because it raises the issues of the difference between the name and the verb.In this study, we tried to analyze the nominal style and its most used linguistic methods such as the exclamations noun sentence, presentation methods and isolated vocabulary by having poems known to be poets of modernity such as Baudelaire, Rambo, Apollinaire and others ....This analysis sheds light on the characteristics of the nominal style addressed at the beginning of the research and reveals to us why poets chose this method as a form of modernity that contributed to the perpetuation of their poems that we are still reading to this day.